Implementation of Problem-Solving Model to Improve Students' Mathematical Problem-Solving Ability at SD Negeri 4 Bandar Baru - Fitri, Nurur; Fitriana (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the mathematical problem-solving skills of fifth-grade students at SD Negeri 4 Bandar Baru through the application of the Problem-Solving learning model. The research was motivated by the fact that many students demonstrated difficulties in understanding mathematical concepts, interpreting problems, and applying appropriate strategies to find solutions. A Classroom Action Research (CAR) design was employed, consisting of two cycles with each cycle including the stages of planning, implementation, observation, and reflection. The participants were 30 students from class V, and data collection was carried out through problem-solving tests, observation sheets, and documentation. The results of the study indicated a significant improvement in students’ mathematical problem-solving abilities. In the preliminary stage, only 36.7% of students achieved the minimum mastery criterion (KKM = 70), with an average score of 62.5. After the first cycle, the average score increased to 73.2 with 66.7% of students meeting the mastery criterion. Further progress was observed in the second cycle, where the average score reached 82.6 and the percentage of students achieving mastery rose to 90%. In addition, students showed higher motivation, better collaboration, and more systematic reasoning in solving mathematical problems. These findings suggest that the Problem-Solving model is effective in enhancing students’ mathematical problem-solving skills and can be implemented as an alternative instructional strategy in elementary mathematics learning.